2022
DOI: 10.1101/2022.12.14.520525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host Immunity toMycobacterium tuberculosisInfection is Similar in Simian Immunodeficiency Virus (SIV)-infected, Antiretroviral Therapy-treated and SIV-naïve Juvenile Macaques

Abstract: Pre-existing HIV infection increases tuberculosis (TB) risk in children. Antiretroviral therapy (ART) reduces, but does not abolish, this risk in children with HIV. The immunologic mechanisms involved in TB progression in both HIV-naïve and HIV-infected children have not been explored. Much of our current understanding is based on human studies in adults and adult animal models. In this study, we sought to model childhood HIV/Mycobacterium tuberculosis(Mtb) coinfection in the setting of ART and characterize T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 93 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…In this study, we sought to boost V9+V2+  T cells, a  T cell subset associated with anti-Mtb activity (14-16), using our nonhuman primate model of pediatric HIV/Mtb coinfection (26) to determine whether augmenting V9+V2+  T cells could reduce Mtb burden and overall TB disease in the presence of a pre-existing SIV infection. Several groups have shown that inducing V9+V2+  T cells by various approaches is moderately efficacious against Mtb infection in SIV-naïve, adult rhesus macaques (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we sought to boost V9+V2+  T cells, a  T cell subset associated with anti-Mtb activity (14-16), using our nonhuman primate model of pediatric HIV/Mtb coinfection (26) to determine whether augmenting V9+V2+  T cells could reduce Mtb burden and overall TB disease in the presence of a pre-existing SIV infection. Several groups have shown that inducing V9+V2+  T cells by various approaches is moderately efficacious against Mtb infection in SIV-naïve, adult rhesus macaques (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that MCM chronically infected with SIV had defective adaptive immune responses to Mtb coinfection (47). Treating SIV-infected juvenile macaques with ART appeared to ameliorate these defects (26). Zhou and colleagues have also shown that SIV infection impairs mycobacterial-specific responses in V2+  T cells (48).…”
Section: Decreased Ccr6 Expression Corresponded With Increased Circul...mentioning
confidence: 97%
See 3 more Smart Citations